we know that the endpoints of AB are
![\begin{gathered} (x_1,y_1)=\mleft(-6,-3\mright) \\ (x_2,y_2)=(-3,-9) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/lendd9tqfajzrmg4661iygo2bfxhjyqfdd.png)
and the distance formula is given by
![d=\sqrt[]{(x_2-x_1)^2+(y_2-y_1)^2}](https://img.qammunity.org/2023/formulas/mathematics/college/be685jmxw05hm2tq94m5iuge2xjynn1hfn.png)
By substituying these points, we have that
![d=\sqrt[]{(-3-(-6))^2+(-9-(-3))^2}](https://img.qammunity.org/2023/formulas/mathematics/college/wi42tgkez07xlpxfmts4jue1h4zdd2l76g.png)
which is equal to
![\begin{gathered} d=\sqrt[]{(-3+6)^2+(-9+3)^2} \\ d=\sqrt[]{3^2+(-6)^2} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/80db8h8rtpllbqtvka0lx1nhgk2l0yr7gv.png)
then
![\begin{gathered} d=\sqrt[]{9+36} \\ d=\sqrt[]{45} \\ d=\sqrt[]{9\cdot5} \\ d=\sqrt[]{9}\cdot\sqrt[]{5} \\ d=3\sqrt[]{5}\ldots..(A) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ntfgnu9b8tzn9f49yni52vyqppfh7p7vtl.png)
On the other hand, if
![\begin{gathered} (x_1,y_1)=(-2,-1) \\ (x_2,y_2)=(-1,-3) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/pbwcuqpjsejfq0szd76uj1dmikqh5imfi8.png)
similarly to the previous case, the distance between the endpoint for A'B' is
![d=\sqrt[]{(-1-(-2))^2+(-3-(-1))^2}](https://img.qammunity.org/2023/formulas/mathematics/college/w1vrfi6u8cz4prq4xt1cb8dlne8fid0b3l.png)
which is equal to
![\begin{gathered} d=\sqrt[]{(-1+2)^2+(-3+1)^2} \\ d=\sqrt[]{1^2+(-2)^2} \\ d=\sqrt[]{1+4} \\ d=\sqrt[]{5}\ldots..(B) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/81w0xcn2pq5csvoaykt3ghzvmkjmfx5pnz.png)
Now, by comparing equation A and equation B, we can see that, the scale factor is 1/3.
Then, the answer is B.